Trusted coalition-proof protocol model based on secure multi-part computing - CHENG Bai-liang1; ZENG Guo-sun1; JIE An-quan2 (Tongxin xuebao)
N parties were involved in the computation of a function,which did not trust each other.Some of them found a coalition and destroy the security of others through collusion.Based on secure multi-party computation and communica-tions channel,to the collusion that could be nested,a trusted coalition-proof protocol model was proposed.The concept of correlated equilibrium was used by the model in game theory for talking place the trusted third party.